A Comparative Study of Salivary pH and Composition between Semi-Vegetarian Dentistry Students from the Adventist University of the Philippines and Omnivore Dentistry Students from the University of the Philippines Manila/ Janine Marie B. Arboleda and Erika Mari B. Castro. - Arboleda, Janine Marie B., Author
Introduction: Salivary biochemical indicators like calcium and phosphate play their respective roles in determining caries susceptibility of an individual (Kaur et al, 2012). The ionic concentration of calcium and phosphate in saliva is responsible for the maintenance of equilibrium between demineralization and remineralization of dental hard tissues within the oral cavity. These salivary parameters can be used as a diagnostic tool for caries risk assessment. This study looked closely at the differences of calcium and phosphate content and pH level of saliva from semi-vegetarian and omnivore participants